2019
DOI: 10.1051/matecconf/201926604003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Trace Metal Contamination in Pahang River and Kelantan River, Malaysia

Abstract: The primary objective of this study is to determine trace metal contamination in environmental samples obtained from Pahang River and Kelantan River, Malaysia which may help to identify the risk of sustainable dredging in these areas. This research also proceeds to compare the trace metal concentration with the National Water Quality Standards of Malaysia, Interim Canadian Sediment Quality Guidelines and Malaysian Food Act 1983 to determine its limits and risks. Samples of water, sediment, snails and fishes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The Kelantan and Pahang Deltas were found to be the main anthropogenic sources of 210 Pb input in the surface sediments of the sSCS, with the Kelantan Delta having a higher average 210 Pb level than the Pahang Delta. According to [12,13], the high level of contaminant present in the both rivers was due to the continuous mining and land clearing which in turn elevating the level of contaminant present in the both riverine. The data showed that stations closest to the river mouth in the deltas had higher 210 Pb concentrations and that this trend decreases with increased distance from the river mouth.…”
Section: Different Input Sources Of 210 Pb and The Roles Of Insitu Pa...mentioning
confidence: 99%
“…The Kelantan and Pahang Deltas were found to be the main anthropogenic sources of 210 Pb input in the surface sediments of the sSCS, with the Kelantan Delta having a higher average 210 Pb level than the Pahang Delta. According to [12,13], the high level of contaminant present in the both rivers was due to the continuous mining and land clearing which in turn elevating the level of contaminant present in the both riverine. The data showed that stations closest to the river mouth in the deltas had higher 210 Pb concentrations and that this trend decreases with increased distance from the river mouth.…”
Section: Different Input Sources Of 210 Pb and The Roles Of Insitu Pa...mentioning
confidence: 99%
“…Manganese able to accumulate for long period and exist in the water, sediments and living things. It is transferred into sediments by physical, chemical or biological processes that can affect living organisms as the waterbody is exposed to the toxic contaminant [42]. Metals tend to accumulate or reacts with particulates and finally settles in bottom sediments of streams.…”
Section: Occurrences Of Manganese Contaminationmentioning
confidence: 99%
“…The toxicity from manganese contamination has endangered marine organisms. The contaminant will accumulate in tissues and organs of aquatic organism which then being consumed by humans and eventually caused long-term health risks to humans [42]. Table 4 shows the adverse effects of manganese exposure.…”
Section: Negative Impactsmentioning
confidence: 99%
“…However, there is no data on the concentration of dissolved metals have been reported during their study. Besides, a few studies related to the trace metals distribution in the area were determined in the fresh water and sediment samples [11][12][13][14][15] . Less study was conducted to identify the concentration of dissolved metals in the estuaries water due to the high chloride ion in the water sample.…”
Section: Introductionmentioning
confidence: 99%